(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
The purpose of this study was to examine in vitro the herbicidal effect of an essential oil of dill (Anethum graveolens) on germination and early seedling growth of two parasitic flowering plants in the genus Cuscuta (Cuscuta campestris and C. epithymum), as well as its phytotoxic impact on germination and early seedling growth of two host plants (alfalfa and red clover). Chemical analysis of the essential oil extracted from dill leaves and flowers showed that carvone (51.69%) and limonene (39.88%) predominated. The results of a seed bioassay showed inhibitory effects of different concentrations (1%, 0.5%, 0.1%, and 0.01% v v-1) of the essential oil of dill leaves on germination and early seedling growth of both tested species of the genus Cuscuta. Germination of C. campestris seeds was inhibited between 67% and 94%, while seed germination of C. epithymum was inhibited between 67% and 100%. A similar inhibitory effect was observed regarding the seedling length parameter. Moreover, the bioassay results indicated significant phytotoxic effects of dill essential oil on the seed germination and early seedling growth of host plants. Red clover proved more sensitive as even the lowest concentration inhibited germination by 35%, while higher concentrations caused 70-100% inhibition. On the other hand, lower concentations inhibited germination of alfalfa seeds by 5%, while higher concentrations caused greater inhibition (36-100%). Future research should include both pot experiments and field micro-trials to determine herbicidal, i.e. phytotoxic, effects of dill essential oil on parasitic flowering plants and cultivated species.